If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6m + 3n + 4m + -9n = 0 Reorder the terms: 6m + 4m + 3n + -9n = 0 Combine like terms: 6m + 4m = 10m 10m + 3n + -9n = 0 Combine like terms: 3n + -9n = -6n 10m + -6n = 0 Solving 10m + -6n = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '6n' to each side of the equation. 10m + -6n + 6n = 0 + 6n Combine like terms: -6n + 6n = 0 10m + 0 = 0 + 6n 10m = 0 + 6n Remove the zero: 10m = 6n Divide each side by '10'. m = 0.6n Simplifying m = 0.6n
| x-3-2/5 | | 4x+x+25=90 | | x+y+2z=3 | | x*0.85+(400-X)*0.05=260 | | 250=5*r | | 6xy(3x^2+4y)= | | 70-2x+5=3x | | -5g-2r-2g-5r= | | 36^5/24^3 | | ln(x)=3.210439862 | | 250=15*t | | 4+-3x^2+x^3=0 | | 1+y+-4z-y+4z=1 | | 2x^3y-16x^2y-18xy= | | 7=3+2g | | 20+4x-6=6x | | 6x+3=8+11 | | 2x+11=-9+8x | | 6x-1=4x-7 | | 16/x=2 | | x-y+4z=1 | | 5d+3x-x-5d= | | 1-2X=X/3-X/2 | | w^2+2x+35=0 | | (y^3)-(3y^2)+(4)=0 | | 8H+7=37-2h | | 5(x+3)-3x=2x+8 | | sqrt(x-3)=sqrt(2x-7) | | (8x-4)(4x+3)=0 | | 4x^3-18x^2+10x= | | 3.8=-k(10) | | 2x+(4-2)=16 |